Normal saline versus lactated Ringer’s solution for acute pancreatitis resuscitation, an open-label multicenter randomized controlled trial: the WATERLAND trial study protocol - Lucía Guilabert; Karina Cárdenas-Jaén; Alicia Vaillo-Rocamora; Ana García García de Paredes; Ankit Chhoda; Sunil G. Sheth; Carlos López-Valero; Pedro Zapater; Eva M. Navarrete-Muñoz; Patrick Maisonneuve; Yasmin G. Hernández-Barco; Gabriele Capurso; et al. (Trials)
Abstract Background Some evidence suggests that fluid resuscitation with lactated Ringer’s solution (LR) may have an anti-inflammatory effect on acute pancreatitis (AP) when compared to normal saline (NS) and may be associated with a decrease in severity, but existing single-center randomized controlled trials showed conflicting results. The WATERLAND trial aims to investigate the efficacy and safety of fluid resuscitation using LR compared to NS in patients with AP. Methods The WATERLAND trial is an international multicenter, open-label, parallel-group, randomized, controlled, superiority trial. Patients will be randomly assigned in a 1:1 ratio to receive LR versus NS-based fluid resuscitation for at least 48 h. The primary outcome will be moderately severe or severe AP, according to the revision of the Atlanta classification. The secondary objectives of the WATERLAND trial are to determine the effect of LR versus NS fluid resuscitation on several efficacy and safety outcomes in patients with AP. A total sample of 720 patients, 360 in the LR group and 360 in the NS group, will achieve 90% power to detect a difference between the group proportions of 10%, assuming that the frequency of moderately severe or severe AP in the LR group will be 17%. A loss to follow-up of 10% of patients is expected, so the total sample size will be 396 patients in each treatment arm (792 patients overall). The test statistic used is the two-sided Z test with pooled variance set at a 0.05 significance level. Discussion The WATERLAND study aims to improve the early management of AP. Fluid resuscitation is an inexpensive treatment available in any hospital center worldwide. If a better evolution of pancreatitis is demonstrated in one of the treatment arms, it would have important repercussions in the management of this frequent disease. Trial registration ClinicalTrials.gov, NCT05781243. Registration date on January 4, 2023. EudraCT number 2023–000010-18, first posted March 23, 2023.